2017
DOI: 10.2134/jeq2016.09.0368
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia and Nitrous Oxide Emissions from Broiler Houses with Downtime Windrowed Litter

Abstract: An emerging poultry manure management practice is in-house windrowing to disinfect the litter. However, this practice is likely to increase emissions of ammonia (NH) and nitrous oxide (NO) from the windrowed litter. The objective of this study was to quantitatively compare NH and NO emissions from broiler houses with and without in-house windrowing. Two broiler houses at a commercial farm were used to compare the NH and NO emissions. Gas emission measurements were conducted continuously and simultaneously for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
3
0
3
Order By: Relevance
“…Therefore, the level of N 2 O measured in broiler houses vary considerably. RO et al (2017) found relatively high N 2 O values in broiler production systems where the litter is composted in between several successive crops. The mean N 2 O emission varied from 4.43 to 3.89 g per bird, depending on the litter management.…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, the level of N 2 O measured in broiler houses vary considerably. RO et al (2017) found relatively high N 2 O values in broiler production systems where the litter is composted in between several successive crops. The mean N 2 O emission varied from 4.43 to 3.89 g per bird, depending on the litter management.…”
Section: Resultsmentioning
confidence: 94%
“…A atmosfera interna afeta diretamente a eficiência, conversão alimentar e emissão de amônia por kg de produto animal. Ro et al (2017) também atribuem uma menor taxa de NH3 à menor umidade e temperatura da cama, logo uma redução nas emissões de N2O pela conversão biológica de NH3 em N2O.…”
Section: Resultsunclassified
“…Se por um lado ocorre a redução daquantidade descartada de cama, por outro o reaproveitamento contínuo para múltiplos alojamentos resulta em aumentos acentuados na concentração de muitos constituintes físico-químicos como nitratos e fósforo que são potencialmente preocupantes para a saúde das aves e do meio ambiente. Ro et al (2017) apontam que o enleiramento interno da cama de frango por aproximadamente 12 dias como tratamento para sua reutilização em respectivos alojamentos apresenta aumento significativo da emissão de NH3 e N2O no meio ambiente. Mesmo indicado pelos serviços de inspeção sanitária como protocolo para controle de surtos e doenças como a gripe aviária, esse manejo deve ser avaliado pelos produtores como prática recorrente na criação de frangos.…”
Section: Resultsunclassified
“…The three-dimensional (3-D) sonic anemometer provided the wind information needed for calculations of friction velocity (u*), Obukhov stability length (L), surface roughness length (z o ), and wind direction. To avoid error-prone periods, the following post data-filtering criteria were used [16]:…”
Section: Sensorsmentioning
confidence: 99%